Relationship Between Dermoscopic Capillary-Related Features of the Auricle and Earlobe and Rosacea Subtype and Disease Severity: A Cross-Sectional Analysis - Zhang Y; Pan R; Gu D; Meng X; Liu T; Xu Y (Dove Medical Press, 2023)
Yue Zhang, Ruoxin Pan, Duoduo Gu, Xiaoqi Meng, Tingwei Liu, Yang Xu Department of Dermatology, The First Affiliated Hospital of Nanjing Medical University, Nanjing, Jiangsu Province, 210029, People's Republic of ChinaCorrespondence: Yang Xu, Department of Dermatology, The First Affiliated Hospital of Nanjing Medical University, No. 300 Guangzhou Road, Nanjing, Jiangsu Province, 210029, People's Republic of China, Tel/Fax +86-13851856794, Email yangxu@njmu.edu.cnBackground and Aim: Clinical manifestations of rosacea include transient or persistent facial erythema, telangiectasia, papules, and pustules. The existing assessment tools primarily evaluate the facial area to assess the severity of rosacea. However, in addition to the face, telangiectasia, erythema, and flushing can occur in the ear. Here, we investigated the correlation between the dermoscopic characteristics of capillaries in the earlobe and auricle and the types and severity of rosacea.Materials and Methods: Experienced dermatologists evaluated the clinical type, medical history, severity, and distribution pattern of facial erythema. The clinical severity of rosacea was assessed using the standard grading system (SGS), clinician's erythema assessment (CEA), and investigator's global assessment (IGA). Relationships of the clinical types and severity with the dermoscopic characteristics of capillaries in the earlobe and auricle were further analyzed.Results: In total, 145 patients with rosacea were enrolled in this study. We found that SGS, CEA, and IGA correlated well with the dermoscopic features of capillaries in the earlobe (R = 0.357, 0.357, and 0.314, respectively) (p < 0.001) and auricle (R = 0.423, 0.443, and 0.374, respectively) (p < 0.001). However, there was no significant correlation between the features and types of rosacea.Conclusion: The dermoscopic characteristics of capillaries in the earlobe and auricle can be used as indicators of the clinical severity of rosacea, regardless of the clinical subtype.Keywords: skin conditions, ear, dermoscopy, blood vessels